Inmates with Dementia: Responding to an Ageing and Ailing Prison Population - Zofia; Joanna (Magyar Gerontológia, 2025)
Penitentiary systems worldwide are confronting a profound demographic shift mirroring that of developed societies: a rapidly ageing prison population. This trend results in a growing number of inmates with complex, age-related health issues, most notably dementia and other severe cognitive impairments.